Strategi Guru dalam Membangun Kemampuan Literasi Matematika pada Peserta Didik Kelas II Sekolah Dasar - Haryati, Alvy; Pramudiani, Puri (Universitas Negeri Padang, 2025)
In the world of mathematics education, developing mathematical literacy skills is crucial. This research aims to describe teachers' strategies for cultivating mathematical literacy skills among second-grade students. The goal of mathematics education is for students to understand and utilize mathematical concepts, solve problems, communicate effectively, apply reasoning, and cultivate a respectful attitude. When individuals encounter mathematical problems, they typically identify, organize, and relate them to their mathematical knowledge. The research employs qualitative methodology with a descriptive approach. The participants included second-grade teachers. Based on the observation results, it can be seen that in the planning phase, the teacher prepares teaching materials such as designing an engaging Learning Implementation Plan that adapts to the students' characteristics. They also prepared learning media and other teaching materials to support the learning process in the classroom, and they use ice breakers to enhance students' enthusiasm for learning both inside and outside the classroom. Additionally, teachers utilized learning media that are appropriate to the material being discussed. Teachers also provide motivation to students, which is defined as a person's internal strength (energy) that facilitates willingness and engagement in activities, originating from within the individual themselves. At the conclusion of the learning process, teachers often administer quizzes both written and verbal. Students who can answer correctly are allowed to go home early, while those who cannot answer correctly participate in remedial activities before dismissal.